2022
DOI: 10.1186/s12862-022-02040-7
|View full text |Cite
|
Sign up to set email alerts
|

The evolution of vitamin C biosynthesis and transport in animals

Abstract: Background Vitamin C (VC) is an indispensable antioxidant and co-factor for optimal function and development of eukaryotic cells. In animals, VC can be synthesized by the organism, acquired through the diet, or both. In the single VC synthesis pathway described in animals, the penultimate step is catalysed by Regucalcin, and the last step by l-gulonolactone oxidase (GULO). The GULO gene has been implicated in VC synthesis only, while Regucalcin has been shown to have multiple functions in mamma… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
12
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 11 publications
(14 citation statements)
references
References 87 publications
0
12
0
Order By: Relevance
“…In addition, a comprehensive search for homologs of the enzymatic constituents of the plant and animal VC synthesis pathways in C. elegans was also performed, revealing that no pathway was present as a complete set [ 115 ]. The loss of the GULO and Regucalcin , is also observed in other nematode species [ 118 ]. Given the evidence, it was suggested that VC synthesis in C. elegans likely occurs through a yet undescribed metabolic pathway [ 115 ].…”
Section: Alternative Animal Vc Synthesis Pathwaysmentioning
confidence: 92%
See 4 more Smart Citations
“…In addition, a comprehensive search for homologs of the enzymatic constituents of the plant and animal VC synthesis pathways in C. elegans was also performed, revealing that no pathway was present as a complete set [ 115 ]. The loss of the GULO and Regucalcin , is also observed in other nematode species [ 118 ]. Given the evidence, it was suggested that VC synthesis in C. elegans likely occurs through a yet undescribed metabolic pathway [ 115 ].…”
Section: Alternative Animal Vc Synthesis Pathwaysmentioning
confidence: 92%
“…A direct involvement of Dca or Regucalcin in VC synthesis would imply that at least the lactonase component of the animal pathway is conserved in D. melanogaster . Using an in silico methodology, both Regucalcin and Dca were inferred to be involved in calcium homeostasis and in the oxidative stress response, but so far, no evidence was found for its involvement in VC synthesis [ 118 ]. The involvement in the calcium homeostasis and in the oxidative stress response are expected given the multiple functions of Regucalcin in vertebrates (reviewed in [ 133 ]).…”
Section: Alternative Animal Vc Synthesis Pathwaysmentioning
confidence: 99%
See 3 more Smart Citations